STRATEGI PEMBERDAYAAN MASYARAKAT DESA BATURETNO BANTUL MELALUI PENDIDIKAN NON FORMAL - Susilo Surahman; Muthia Rahman Nayla (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2022)
Community empowerment is an economic development concept that summarizes society's values to build a new paradigm in development that is people-centered, participatory. This study examines every process of community empowerment through non-formal education programs in the village of Baturetno, Banguntapan, Bantul, DI Yogyakarta. This activity is a development of community service. The community empowerment program results indicate that there are exogenous (government) and endogenous (community) factors in determining the program's success. The function of empowerment and other support is only a companion in line with the mentoring function concept. It is necessary to strengthen awareness, cooperation, and more active communication in improving the welfare of the economy, education, social, culture, and village infrastructure.